A hormonal cue promotes timely follicle cell migration by modulating transcription profiles. (December 2017) - Manning, Lathiena; Sheth, Jinal; Bridges, Stacey; Saadin, Afsoon; Odinammadu, Kamsi; Andrew, Deborah; Spencer, Susan; Montell, Denise; Starz-Gaiano, Michelle
Abstract: Cell migration is essential during animal development. In the Drosophila ovary, the steroid hormone ecdysone coordinates nutrient sensing, growth, and the timing of morphogenesis events including border cell migration. To identify downstream effectors of ecdysone signaling, we profiled gene expression in wild-type follicle cells compared to cells expressing a dominant negative Ecdysone receptor or its coactivator Taiman. Of approximately 400 genes that showed differences in expression, we validated 16 candidate genes for expression in border and centripetal cells, and demonstrated that seven responded to ectopic ecdysone activation by changing their transcriptional levels. We found a requirement for seven putative targets in effective cell migration, including two other nuclear hormone receptors, a calcyphosine-encoding gene, and a prolyl hydroxylase. Thus, we identified multiple new genetic regulators modulated at the level of transcription that allow cells to interpret information from the environment and coordinate cell migration in vivo. Highlights: Varied categories of genes transcriptionally respond to EcR and Tai signaling in ovarian follicle cells. Proper border cell migration requires signaling from additional nuclear hormone receptors. Prolyl-4-hydroxylase alpha EFB ( PH4αEFB ) acts to synchronize cell migration and egg development.